Artistic Psychologism in Isajon Sultan's Work "Alisher Navoi" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
When we read any literary work, we see that the writer approaches the characters in various ways to demonstrate its artistry. Plastic elements play a special role and achieve perfection in verbally portraying the characters' feelings and thoughts before the reader's eyes, enhancing the work's vividness. In this respect, these elements contribute to the unique manifestation of artistic psychologism in the work.